Change of Dye Bath for Sensitisation of Nanocrystalline TiO2 Films: Enhances Performance of Dye-Sensitized Solar Cells. (24th July 2011) - Chandrasekharam, Malapaka; Rajkumar, Ganugula; Rao, Chikkam Srinivasa; Reddy, Paidi Yella; Kantam, Mannepalli Lakshmi
Abstract : The photovoltaic performance of the heterolepticH 102 andHRD 2 sensitizers was measured in DSSC and compared with that of reference N719 under similar fabrication and evaluation conditions. The Dye-Sensitised TiO2 electrodes were prepared by staining the electrodes in ethanol bath and 1/1 v/v acetonitrile/ tert -butanol (binary liquid) mixture bath separately and the DSSCs based on these sensitizers show that the change of dye bath from ethanol to the binary liquid mixture enhances the photocurrent action spectrum and solar-to-electricity conversion efficiencies, ( η ). Using ethanol for sensitisation of TiO2 electrodes, the efficiencies obtained forH 102, HRD 2 and N719 are 4.31%, 4.62%, and 5.46%, respectively, while in binary liquid mixture bath, the corresponding values are enhanced to 5.89%, 4.87%, and 7.23%, respectively, under comparable conditions.